New Insect Problems in Arid Ecosystem - Verma, S K (Annals of Arid Zone, 2016)
Changes in cr0pping systems and introduction of unconventional crops in western Rajasthan over the past four decades have appreciably changed the pest complex. Insects with tendencies of polyphagy appear to have shifted their preferences. Seasonality of the appearance of scarab adults and damage by root grubs have changed due to introduction of canal irrigation in the region. Castor defoliator Achaea janata is now established as a severe pest of henna (Lawsonia spp.) and it also attacks senna (Cassia angustifolia). Papilio polytes and P. demoleus are recorded on Aegle marmelos and Iv/urraya koenigi. Changes in the pestilence behavior of scarabs. accentuation of sucking pests and alternate hosts are discussed. Some other new records now reported include ilmblyrhinus poricollis weevils on jujube: psylla Diaphorina cardiae, sphingids Polypticus dentatus and Psilogramma menephron on sebesten (Cordia dichotoma); Maladera nathani (grubs) on sweet potato: Acaudaleyrodes rachipora (=citri) on clusterbean: Pachyrrhinadoretlls sp. beetles. coreid Mirperus jaculus. Sogatel/a vibix: 'chloropid Anacamptoneurum ob/iquum (maggots) on pearl millet. pseudococcid Ferrisia virgata on henna. Creatonotlls gangis on mung bean and moth bean; and Aphis craccivora on clusterbean.